Matching Supply and Demand of Ecosystem Services in the "Mountain-Oasis-Desert" System: A Case Study of the Heihe River Basin - Zhang, Yawen; Bai, Yongping (Scientific Journal of Technology, 2025)
The Heihe River Basin was selected as the study area in this paper. Based on spatial and statistical data, the InVEST model and related formulas were used to quantify the supply and demand of four ecosystem services: Water Yield (WY), Soil Retention (SR), Carbon Sequestration (CS), and Food Production (FD). Using these results, the supply-demand ratio and Z-score standardization were applied to analyze the matching of supply and demand for ecosystem services in the basin. Finally, the driving factors affecting the ecosystem service supply-demand ratio were explored by using Geo Detector. The results indicated that: (1) The spatial pattern of ecosystem service supply and demand in the Heihe River Basin exhibited significant gradient differentiation and spatial heterogeneity. Overall, the total supply of three ecosystem services: Soil Retention (SR), Carbon Sequestration (CS), and Food Production (FD) exceeded their total demand; in contrast, the total supply of Water Yield (WY) services fell short of demand. (2) The supply and demand of ecosystem services in the basin exhibit a spatial gradient pattern of "mountain surplus - oasis balance - desert deficit". The mountain subsystem is dominated by high supply-low demand(H-L) and high supply-high demand(H-H) matching types; in contrast, in contrast, the oasis subsystem features mixed-type matches, and the desert subsystem is characterized by low supply-low demand (L-L) matching types. (3) The supply-demand ratios of ecosystem services in the Heihe River Basin are primarily influenced by socio-economic factors such as population density (POP) and GDP.